2019
DOI: 10.1080/22221751.2019.1663131
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the H7 HA and PB1 genes of avian influenza a viruses increase viral pathogenicity and contact transmission in guinea pigs

Abstract: Avian influenza A viruses (AIV) of the H7 subtype continue to evolve posing a pandemic threat. However, molecular markers of H7N7 AIV pathogenicity and transmission in mammals remain poorly understood. In this study, we performed a systematic in vitro and in vivo analysis by comparing an H7N7 highly pathogenic AIV and its ferret adapted variant. Passaging an H7N7 AIV in ferrets led to six mutations in genes encoding the viral polymerase complex and the viral surface proteins. Here, we show that mutations in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
0
5
0
1
Order By: Relevance
“…7 Mutations in the polymerase genes of viruses are reported to enhance their virulence. [8][9][10] Mutations in the RdRp gene sequence were first reported in virus isolates from Europe in February 2020, and then in virus isolates from North America in March 2020. 2 In particular, a mutation at position 14408, which leads to an amino acid substitution (P323L) in RdRp, was identified as a mutation hotspot, and in silico analysis suggests that this change may affect stability of the tertiary complex of RdRp.…”
Section: Introductionmentioning
confidence: 99%
“…7 Mutations in the polymerase genes of viruses are reported to enhance their virulence. [8][9][10] Mutations in the RdRp gene sequence were first reported in virus isolates from Europe in February 2020, and then in virus isolates from North America in March 2020. 2 In particular, a mutation at position 14408, which leads to an amino acid substitution (P323L) in RdRp, was identified as a mutation hotspot, and in silico analysis suggests that this change may affect stability of the tertiary complex of RdRp.…”
Section: Introductionmentioning
confidence: 99%
“…Lina et al employed guinea pigs to show that adaptive amino acid substitutions account for the increased transmissibility of H9N2 avian influenza virus [109]. Mutations in the HA and PB1 genes were also demonstrated to increase pathogenicity and transmissibility of influenza viruses in the guinea pig model [110,111]. Previous studies using guinea pigs have shown that IAVs are transmissible via aerosolized fomites, microscopic particulates released from virus-contaminated surfaces (such as fur, skin, or bedding) [112], or respiratory droplets [113].…”
Section: Guinea Pig Modelmentioning
confidence: 99%
“…Вирусы ВПГП подтипа Н5 способны инфицировать человека, несмотря на то что их гемагглютинин преиму щественно взаимодействует с клеточными рецептора ми SAα2,3gal. Однако при успешной репродукции ви руса гриппа в клетках млекопитающих исследователи выявляли мутации в других вирусных генах, которые предполагаются как маркеры адаптации вируса гриппа для размножения в организме млекопитающих [6][7][8][9][10][11]…”
Section: Conflict Of Interestunclassified